The Role of Tumor-Infiltrating B Cells in Tumor Immunity. (24th September 2019) - Guo, Fei Fei; Cui, Jiu Wei
Abstract : Earlier studies on elucidating the role of lymphocytes in tumor immunity predominantly focused on T cells. However, the role of B cells in tumor immunity has increasingly received better attention in recent studies. The B cells that infiltrate tumor tissues are called tumor-infiltrating B cells (TIBs). It is found that TIBs play a multifaceted dual role in regulating tumor immunity rather than just tumor inhibition or promotion. In this article, latest research advances focusing on the relationship between TIBs and tumor complexity are reviewed, and light is shed on some novel ideas for exploiting TIBs as a possible tumor biomarker and potential therapeutic target against tumors.